Advances in the applications of biomass-derived carbon materials in triboelectric nanogenerators - Jie WU; Ao SONG; Yunchao LI; Dingkun YUAN; Shahong ZHU; Guangxue ZHANG; Jiangrong XU (能源环境保护)
Triboelectric nanogenerators (TENGs), which convert mechanical energy into electrical energy, have been applied in the fields of wearable devices, environmental monitoring, and energy harvesting. In recent years, many researchers have utilized biomass-derived carbon materials (BDCMs) for the development of high-performance TENGs due to their wide range of sources, green environmental protection, and good electrical conductivity. This paper provides a brief introduction to the concepts of TENGs and BDCMs, followed by a summary of several carbonization methods used in the preparation of BDCMs, including pyrolytic carbonization, hydrothermal carbonization, and laser-induced carbonization. The regulation methods for the structure of BDCMs are also discussed, including the use of template and activation methods. The selection of suitable carbonization and regulation methods helps to adjust the specific surface area and pore structure of BDCMs, thereby further improving the output performance, including open circuit voltage and short circuit current, and stability of BDCMs-based TENGs. The paper presents a comprehensive review of the research and application progress of BDCMs-based TENGs in energy-supplying devices and sensing devices. Various biomass materials such as garlic shells, coffee grounds, and eggshell membranes have been successfully used in the manufacture of TENGs and have found applications in energy harvesting, electricity supply, health monitoring, and gesture recognition. Finally, the paper discusses the problems existing in the application of BDCMs in TENGs, providing reference for the innovative use of BDCMs.